2015
DOI: 10.3141/2522-11
|View full text |Cite
|
Sign up to set email alerts
|

Finding Best Model to Forecast Construction Duration of Road Tunnels with New Austrian Tunneling Method Using Bayesian Inference

Abstract: Forecasting project final duration (i.e., time at completion) is crucial to project risk management and is always sought by project managers during the construction period. Because of a strong correlation between past and future performances in linear projects, past progress data are the best source of information to forecast final duration of this type of project, including tunneling projects constructed by the new Austrian tunneling method (NATM). Bayesian inference is a robust probabilistic approach that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Long and Ohsato (2009) introduced a new method for scheduling repetitive construction projects with several objectives including project duration, project cost or both of them and based on genetic algorithms. Hosseinian and Reinschmidt (2015) research was aimed at finding a best progress model for tunneling projects with the new Austrian tunneling method (NATM) by conducting Bayesian analysis on available data of a massive project. The analysis revealed that the dual Gompertz function was the most reliable model for this purpose.…”
Section: Project Duration Prediction Modelsmentioning
confidence: 99%
“…Long and Ohsato (2009) introduced a new method for scheduling repetitive construction projects with several objectives including project duration, project cost or both of them and based on genetic algorithms. Hosseinian and Reinschmidt (2015) research was aimed at finding a best progress model for tunneling projects with the new Austrian tunneling method (NATM) by conducting Bayesian analysis on available data of a massive project. The analysis revealed that the dual Gompertz function was the most reliable model for this purpose.…”
Section: Project Duration Prediction Modelsmentioning
confidence: 99%
“…Related studies in project progress concentrated on its development and for predicting final duration of project progress have been conducted. Hosseinian and Reinschmidt (2015) predicted project final duration, which is the time span used to finish the progress of the project by the means of Bayesian inference. Bayesian inference is referred to as a strong probability-based approach for providing the final outcome of the progress considering the previous performance of the project.…”
Section: Physics' Basic Principlesmentioning
confidence: 99%
“…As shown in Table 1, numerous articles were found in regard to the prediction of actual road construction duration, four that address risk analysis and/or allocation and two that aim to predict expected extensions of time (EoT). Other studies related to construction time for road projects were found, but these dealt with scheduling, control or forensic evaluation techniques and their application to the complexities of specific aspects of road construction such as excavations [11], tunnels [12] or bridges [13].…”
Section: Introductionmentioning
confidence: 99%